Os usos do nome: identidade, estado civil e ordem pública - Edgard Audomar Marx Neto (2013)
The subject of this thesis is the right to the name of the natural person, with emphasis on the possibilities and limitations for its determination and change. The name composes personal status and comprises personal identity. The concept of personal status was built from the elements that indicate the qualification of the person in society, with an emphasis on its integration in the family. Public policy, understood as limitation to private autonomy, is the foundation for the submission of the legal regime of the name to registration. The right to free development of personality, which stems from the protection of human dignity, must conduct the design of the content of public policy. Therefore, the legal protection of the name is designed to guarantee the protection of personal identity. In this research, the author performed dogmatic and sociological analyzes, being necessary the use of primary and secondary data, such as judicial decisions and the bibliography on the subject. The procedure adopted was descriptive, comparative and propositional, based on the current legal regime. The conclusion was that the characterization of the right to the name as a personality right determines the recognition of expanding the scope of private autonomy in itsmanagement and changing. The change of name should not be treated as exceptional and the convenience of reasons for an alteration should not be subjected to the control of the Judiciary, which should only inquire about the effects produced on third parties and the prevention of fraud. In these limits, the name translates personal status and, therefore, becomes an expression of personal identity.